Furunkel Folikulitis Et Tinea Corporis - Wizar Putri Mellaratna; Indri Yustati Ritonga (Jurnal Anestesi, 2023)
Folliculitis is a bacterial skin infection caused by Staphylococcus aureus and Streptococcus sp. If the surrounding tissue is also affected, it is called a furuncle. About 20% of individuals have S. aureus colonization, while S.aureus carriers are found in 60% of healthy individuals.